The Relationship between Spiritual Well-Being and Happiness: An Investigation on Teachers - Mustafa Özgenel; Özden Yılmaz (Spiritual Psychology and Counseling, 2020)
This study aims to examine the relationship between teachers’ spiritual well-being and happiness levels. Being quantitative in nature, this study employs a relationship survey model. A total of 390 teachers employed in various grades of different types of schools (i.e., primary schools, middle schools, Imam-Khatib middle schools, Anatolian-science high schools, Imam-Khatib high schools, and vocational high schools) in Istanbul’s Küçükçekmece district volunteered to participate in this study. The Personal Information Form, the Spiritual Well-Being Scale, and the Oxford Happiness Questionnaire were employed to collect data, which were then analyzed using Pearson’s correlation coefficient and a regression analysis. The results of these analyses reveal that happiness is significantly and positively correlated with transcendence and harmony with nature whereas happiness is significantly and negatively correlated with anomie. While transcendence positively affects teachers’ happiness, anomie negatively affects them. It has been found that this effect size is medium. Another important finding obtained in the study is that harmony with nature, one of the sub-dimensions of spiritual well-being, does not affect teachers’ happiness.